Comparison of Sand Pillows and Cold Compresses in Reducing The Incidence of Hematoma in Post Percutaneous Coronary Intervention (PCI) Patients: A Scoping Review - Qomaruddin Asy’ary; Titin Andri Wihastuti; Dina Dewi Sartika Lestari Ismail (Jurnal Health Sains, 2024)
Coronary heart disease is the most common cause of morbidity and death in the world. Cardiac catheterization is applied to diagnose and treat coronary heart disease. Non-invasive Percutaneous Coronary Intervention (PCI) aims to open narrowed coronary blood vessels. The most frequently used vascular installation site is the femoral artery. The PCI procedure has several vascular complications, such as hematoma, which often occur in post-PCI patients. Using sand pillows and cold compresses is one measure to reduce the incidence of hematomas. This study aims to compare the effectiveness of sand pillows and cold compresses in reducing hematomas in post-PCI patients. This study was designed as a scoping review. Article searches were limited to 2019-2024. Search using the Google Scholar, ScienceDirect, and Proquest databases and using advanced search with the keywords "sandbag," "cold pack," "hematoma," and "percutaneous coronary intervention." A total of 45 articles were found, and then by applying the specified inclusion criteria, we found 6 articles. The 6 articles obtained show that using a sand pillow can reduce the duration of compression and speed up the achievement of hemostasis by pressing on the arteries. Meanwhile, using cold compresses and cold packs can cause vasoconstriction of blood vessels, speed up blood clotting time, and form blood clots. It can be concluded that cold compresses are more effective in reducing the incidence of hematomas in post-PCI patients compared to using sand pillows.